KERAGAMAN FENOTIPE TANAMAN KENARI (Canarium sp.) PADA KEBUN KOLEKSI DI DESA HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Rianekuay, Elva Dasilvia; Matinahoru, Johan M.; Sahupala, Andjela (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aims to analyze the phenotypic diversity of canary plants (Canarium sp.) from three provenances, namely Ambon, Saparua, and Seram, and to observe the relationship between environmental factors and the growth of canary plants in the Canary Collection Garden owned by the Maluku Provincial Forestry Service, located in Hatusua Village, Kairatu District, West Seram Regency. This study used a descriptive method and a completely randomized design (CRD) with ANOVA analysis, multiple regression, and cluster analysis to evaluate phenotypic characters (leaves, stems, fruits/seeds) and environmental factors (light, temperature, humidity, soil pH, fertility, and soil moisture). The results showed that there were significant differences in leaf phenotypic characters (area, length, width), and most of the differences in stem and fruit/seed size were caused by environmental factors. Seram provenance showed greater leaf area and seed weight than Ambon and Saparua. However, the ANOVA results showed that only leaf area showed a significant effect of provenance treatment. Meanwhile, the relationship between vegetative growth (number of branches, stem diameter, and branch-free height) and environmental factors showed varying correlations, depending on the provenance. Cluster analysis grouped the Ambon and Saparua provenances into a phenotypically similar group, while Seram formed a separate cluster.